APLIKASI MULSA SERBUK GERGAJI DAN URIN SAPI YANG TELAH DIFERMENTASI PADA BIBIT KAKAO (Theobroma cacao L.) - Viantika, Yinda; Armaini, Armaini; Isnaini, Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aims to determine the interaction of sawdust mulch and fermented cow urine and to get the best dose to the cocoa seedlings growth.This study has been conducted at the Experimental Garden, Faculty of Agriculture, University of Riau fromJune to October 2016 using Completely Randomized Design 2 factors of ie : (1) thedose of sawdust mulch(0, 150, 250, 350 g/polybag)and (2)fermented cow urine (concentration 0, 10, 20, 30%) with 3 replications. Each experimental unit consisting of 2 sample, so it takes 96 seeds.The parameters were observed are temperature and humidity, observation of growth, plant height, girth trunk, number of leaves, root volume, dry weight seedlings and shoot and roots ratio.The results showed that the interaction of sawdust mulch dose of 150 g/polybag and fermented cow urine concentration of 30% significantly a effect on roots ratio. Sawdust mulch gives the best treatment results with dose of 350 g/polybag effect on temperature and humidity, number of leaves and root volume. Cow urine concentration 0f 30% gives the best results in improving plant height, girth trunk, number of leaves and dry weight seedlings. Keywords:Sawdust Mulch, Fermented Cow Urine, Cocoa Seedlings